Spectroscopic Survey of Eclipsing Binaries with a Low-cost Echelle Spectrograph: Scientific Commissioning. (10th June 2016) - Kozłowski, S. K.; Konacki, M.; Sybilski, P.; Ratajczak, M.; Pawłaszek, R. K.; Hełminiak, K. G.
Abstract: We present scientific results obtained with a recently commissioned échelle spectrograph on the 0.5 m Solaris-1 telescope in the South African Astronomical Observatory. BACHES is a low-cost slit échelle spectrograph that has a resolution of 21, 000 at 5500 Å. The described setup is fully remotely operated and partly automated. Custom hardware components have been designed to allow both spectroscopic and photometric observations. The setup is controlled via dedicated software. The throughput of the system allows us to obtain spectra with an average signal-to-noise ratio of 22 at 6375 Å for a 30 minute exposure of a V  = 10 mag target. The stability of the instrument is influenced mainly by the ambient temperature changes. We have obtained radial velocity (RV) rms values for a bright ( V = 5.9 mag) spectroscopic binary as good as 0.59 and 1.34 km s −1 for a V = 10.2 mag eclipsing binary. RV measurements have been combined with available photometric light curves. We present models of six eclipsing binary systems, and for previously known targets, we compare our results with those available in the literature. Masses of binary components have been determined with 3% errors for some targets. We confront our results with benchmark values based on measurements from the HARPS and UCLES spectrographs on 4 m class telescopes and find very good agreement. The described setup is very efficient and well suited for a spectroscopic survey. We can now spectroscopically characterize about 300 eclipsing binary stars per year up to 10.2 mag assuming typical weather conditions at SAAO without a single observing trip.